MOVE YOUR MIND - BRACKS, NICK (JOHN WILEY, 2021)
Learn how to create new daily habits that build happiness and reduce stress In Move Your Mind, acclaimed actor, entrepreneur, and mental health advocate Nick Bracks delivers the practical tools and lessons that will help you make small, but measurable, daily changes to foster positive, lasting improvements to your mental health. Told through the author's own experiences with mental illness, this book offers a holistic approach to improving your mental health, and shows readers how to make positive lifestyle changes in areas like exercise, nutrition, sleep, mindfulness, and meditation. The book offers: Valuable and insightful case studies of real and well-known people who took control of and improved their mental wellbeing Key research findings from industry leaders in mindfulness, meditation, memory, mental health, psychology, and performance Guidance on how to take small, gradual steps that lead to big changes in your motivation and inspiration Perfect for anyone who has tried to take ownership of their own mental health but lacked the time, motivation, or information to effectively make a change, Move Your Mind is an indispensable guide to creating long-term behavior changes that promote increased happiness, decreased anxiety and stress, and better relationships.